Microbial consortium identification in constructed wetlands of horizontal subsurface flow fed with industrial wastewater colored (2016)
(Eng) In this research, a microbial consortium was isolated from pilot-scale horizontal subsurface flow-constructed wetlands treating rich dye textile wastewater. Wetlands were planted with Phragmites australis, and some parameters,including COD, BOD5, total solids, total suspended solids, total dissolved solids, nitrates, total phosphorus, and metals (Fe, Mn, Zn, Cu, Pb), were monitored in water. Microbial consortia were isolated using an enrichment technique, featuring a mix of four dyes. A total of 24 consortia were isolated with removal percentages above 50%. The consortium with the best dye removal percentage was selected for identification by molecular techniques. This microbial consortium was composed of three different fungus strains and one bacterial strain (Rhodotorula mucilaginosa, Galactomyces pseudocandidum, Rhodotorula sp., and Escherichia coli, respectively). On average, removals of COD above 50% and BOD5 above 80% were obtained. Of the five metals evaluated, only Mn and Pb traces were found.